2002
DOI: 10.1002/cne.10358
|View full text |Cite
|
Sign up to set email alerts
|

Correlated morphological and chemical phenotyping in myenteric type V neurons of porcine ileum

Abstract: The study was aimed at the immunohistochemical characterization of myenteric Stach type V neurons of the pig ileum that were not included in the widely used Dogiel classification. So far, this conspicuous population has been defined morphologically on the basis of silver-impregnated specimens only. By using neurofilament immunohistochemistry, type V neurons that occur singly or in aggregates could be identified unequivocally and could be distinguished from other smoothly contoured myenteric neurons, i.e., type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 36 publications
0
24
1
Order By: Relevance
“…Moreover, the coreactivity for CGRP and SOM could be shown to occur exclusively in myenteric type V neurons. Since we also found numerous CGRP/SOM-reactive boutons closely apposing type V neurons, we suggested that these neurons may be descending interneurons provided that there are no submucosal or extrinsic CGRP/SOM-coreactive neurons which project onto type V neurons [Brehmer et al, 2002b].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, the coreactivity for CGRP and SOM could be shown to occur exclusively in myenteric type V neurons. Since we also found numerous CGRP/SOM-reactive boutons closely apposing type V neurons, we suggested that these neurons may be descending interneurons provided that there are no submucosal or extrinsic CGRP/SOM-coreactive neurons which project onto type V neurons [Brehmer et al, 2002b].…”
Section: Introductionmentioning
confidence: 94%
“…Myenteric type V neurons, projecting mainly anally, are immunopositive for two different forms of choline acetyltransferase (ChAT; the common variant cChAT and the peripheral variant pChAT) [Tooyama and Kimura, 2000] and also display immunoreactivities for enkephalin (ENK), calcitonin gene-related peptide (CGRP) and somatostatin (SOM) [Brehmer et al, 2002b[Brehmer et al, , 2004b. Moreover, the coreactivity for CGRP and SOM could be shown to occur exclusively in myenteric type V neurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scale bar 5 50 mm. (Stach, 1989;Brehmer et al, 2002aBrehmer et al, , 2002b. The fact that among 50 randomly selected CGRP-reactive neurons, many more were type II neurons in comparison to type V, reflects their quite different proportions in ileal myenteric ganglia: between 7 and 8% of the total population were found to be type II neurons, whereas less than 1.5% were type V neurons (Brehmer et al, 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…However, the same observation (type V neurons outlined by CGRP-reactive boutons, type II neurons not outlined) was made in ultrastructural studies without colchicine pretreatment (Brehmer, 2006). The close topographical vicinity between CGRP-reactive boutons and type V neurons may indicate an interneuronal role for this population (Brehmer et al, 2002a). That we have found no aggregated type V neurons among the 150 ileal CGRP-reactive neurons selected is surely a mere coincidence.…”
Section: Discussionmentioning
confidence: 99%